(untitled) (Canadian Medical Education Journal, 2022)
The use of quantitative intercoder reliability measures in the analysis of qualitative research data has often generated acrimonious debates among researchers who view quantitative and qualitative research methodologies as incompatible due to their unique ontological and epistemological traditions. While these measures are invaluable in many contexts, critics point out that the use of such measures in qualitative analysis represents an attempt to import standards derived for positivist research. Guided by extant research and our experience in qualitative research, we argue that it is possible to develop a qualitative-based measure of intercoder reliability that is compatible with the interpretivist epistemological paradigm of qualitative research. We present eight qualitative research process-based guidelines for evaluating and reporting intercoder reliability in qualitative research and anticipate that these recommendations will particularly guide beginning researchers in the coding and analysis processes of qualitative data analysis.